New record of Rhinolophus chiewkweeae (Chiroptera: Rhinolophidae) from the east coast of Peninsular Malaysia with new information on their echolocation calls, genetics and their taxonomy - Morni, Muhd Amsyari; Tahir, Nurul Farah Diyana Ahmad; Rosli, Qhairil Shyamri; Dee, Julius William; Azhar, Isham; Roslan, Azuan; Zahidin, Muhamad Aidil; Abdullah, Mohd Tajuddin; Khan, F. A A (National University of Singapore, 2016)
We present a range extension for a little known species, Rhinolophus chiewkweeae, in the east coast of Peninsular Malaysia. The new locality record for this species in the east coast was at Sungai Buweh, Tasik Kenyir, Terengganu. This represents the seventh known locality in Malaysia for this distinctive species. The echolocation call of the species was recorded for the first time from four individuals with constant frequency ranging from 53.6 to 54.7 kHz (n = 4). This study provides the first genetic information (cytochrome oxidase I) of the species in order to discriminate between members of the pearsoni species group (R. pearsoni, R. chiewkweeae and R. yunanensis), which are morphologically similar. We provide evidence that R. pearsoni is a sister taxon of R. chiewkweeae with a genetic divergence of 12% whereas no information was available from R. yunanensis for comparison. The information on the species taxonomy based on morphological and ecological data are provided. This discovery indicates that this species are more widely spread than previously thought. Additionally, it provides information that can be used to predict the potential distribution of this little known species elsewhere, especially in Peninsular Malaysia, which can consequently assist in its conservation.